2015
DOI: 10.1016/j.aej.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Microcellulose particles for surface modification to enhance moisture management properties of polyester, and polyester/cotton blend fabrics

Abstract: In this work we studied the effect of surface treated fabric by applying Microcrystalline Cellulose (MCC) Particles using two different procedures. The first method was to dissolve MCC particles and form a MCC solution which further was blended with a textile binder to obtain the fabric coating. The second treatment was direct blending MCC particles with same textile binder in order to get the fabric finishing to be sprayed on the fabric surface. The percentage of MCC particles was chosen 6%, as this ratio can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 29 publications
(31 reference statements)
3
22
0
Order By: Relevance
“…The analysis showed that cotton is rougher and softer than polyester, so it had the ability to retain magnetic microparticles more easily when using the K-bar to apply the magnetic coating. In addition, due to the larger contact angle value for polyester compared to the cotton, 16 the Polyester Plain woven 10 9…”
Section: Resultsmentioning
confidence: 99%
“…The analysis showed that cotton is rougher and softer than polyester, so it had the ability to retain magnetic microparticles more easily when using the K-bar to apply the magnetic coating. In addition, due to the larger contact angle value for polyester compared to the cotton, 16 the Polyester Plain woven 10 9…”
Section: Resultsmentioning
confidence: 99%
“…Step 5. The weighted normalized value υ ij was calculated as in equation (7), where W i was the weight of the i-th attribute of the criterion and…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, so far, some scholars have been investigating the performance of the surface modifications and the wicking treatments on the mentioned properties. [2][3][4][5][6][7][8] Hygienic comfort is an important phenomenon, especially for activewear and sportswear clothing made of synthetic fibers, wherein sweat should be immediately removed from the body in order not to let bacteria proliferate and create unpleasant odor. [9][10][11][12][13][14] Highly hydrophobic inherent characteristics of most synthetic fibers make them resistant to microbes.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known by its hydrophobic (low moisture regain) and electrostatic nature. To obtain better moisture transport, researchers are thinking to modified polyester, especially with using multifilament and fine filament yarns [8][9]. Multifilament polyester yarns are made by aggregating many continuous filaments together.…”
Section: Introductionmentioning
confidence: 99%